ROLE OF INNOVATION CAPABILITY IN INCREASING SHAREHOLDER VALUE (SALES GROWTH AS INTERVENING VARIABLE) - Masmira Kurniawati (Journal of Management and Business, 2014)
This study aims to demonstrate that innovation capability as one of companies’ marketing capabilities has an important role in increasing shareholder value through superior market performance, i.e. the sales growth. Recently, there has been increasing number of researches conducted in investigating the link between marketing performance and stock market performance in Indonesia. These are very important especially for companies listed in Indonesia Stock Exchange. In general, this study tries to develop, test, and find empirical support the relationship between innovation capabilities and shareholder value. The data used are secondary data from the financial statements of Unilever Company. Data were analyzed using mediation analysis suggested by Baron and Kenny (1986). The results of this study provide insight about the relationship between innovation capability and shareholder value. Managerial implications and suggestions for future research will then be delivered.